MICROWAVE INDUCED PYROLYSIS FOR BIO-OIL PRODUCTION FROM LIGNOCELLULOSIC BIOMASS - AHMAD AFIF, HAFIZAH (2015)
Pyrolysis is a process where the decomposition of material occurs at elevated temperature (typically at around 300 to 650 °C) in the absence of an oxidizing agent. The pyrolysis of biomass by means of conventional heating is found to be slow due to the biomass has relatively high moisture and low heating value that would slow down the heating process. In order to overcome this issue, microwave induced pyrolysis was introduced in this study to decompose biomass into chemical compound. The microwave, heats effectively by delivering energy to material through molecular interaction with electromagnetic field and transfers energy throughout the volume of material. Volumetric heating is the key to reduce the processing time. Ten types of biomass that are available in Malaysia were used in the study such as oil palm kernel shell, oil palm leaves, empty fruit bunches, oil palm frond, rubber seed inner shell, rubber seed outer shell, corn cob, sugarcane bagasse, rice husk and coconut shell.